Secularization and the Loss of Love in Bunyan’s Pilgrim’s Progress - Boscaljon, Daniel (Religions, 2013)
In this paper, I place Bunyan’s popular Pilgrim’s Progress into a cultural context infused with, and informed by, a change from a sacred to secular preunderstanding. I discuss the ways that Bunyan wrestles with these changes in light of Taylor’s work on secularization, and theorize that Bunyan’s text reveals how the sacred and secular imaginaries were able to merge through a shared embrace of an economic system of rationalization. Additionally, and more tragically, both ideologies share a disdain for love in its vulnerable, intimate, and material forms that has led us to desire security instead of attending to a more humble (but powerful and enriching) need for assurance. I conclude by discussing Adorno’s discussion of love and Auschwitz as a warning still necessary in our 21st century secular age.